Breakdown Characteristic Research on Propylene Carbonate After Nano-Modification - Zicheng, Zhang; Diangeng, Li; Yanpan, Hou (Frontiers in Physics, 2022)
Propylene carbonate (PC), has the advantages of great permittivity, high dielectric insulating strength and wide range of environmental adaption. However, the applications of propylene carbonate in pulsed power system has been restricted by the significant polarity effect (differences between the positive breakdown strength in positive polarity and the negative breakdown strength). In this paper, the breakdown characteristics of PC under microseconds pulse have been systematically studied by adding nano-particles. The results show that the breakdown strength of pure PC in the positive polarity is about twice that of the negative polarity. While after nano modification, the breakdown strength in the negative polarity increases significantly with the breakdown strength in the positive polarity decreases significantly, which significantly reduces the difference of withstand voltage. In additon,the nano-particles can reduce the dielectric strength difference between the cathode and anode under the quasi homogeneous field. The energy band theory of nano-fluids (NFs) was established to analyze the breakdown characteristics of NFs.